1993
DOI: 10.1084/jem.178.6.1845
|View full text |Cite
|
Sign up to set email alerts
|

The giant organelles in beige and Chediak-Higashi fibroblasts are derived from late endosomes and mature lysosomes.

Abstract: SummaryChediak-Higashi Syndrome (CHS) is an autosomal recessive disease affecting secretory granules and lysosome-like organelles . In CHS fibroblasts, acidic organelles are abnormally large and clustered in the perinuclear area. We have analyzed fibroblast cell lines from a CHS patient and from the murine model for CHS, the beige mouse, to determine which lysosome-like compartments are affected. Uptake of neutral red showed that in both beige and CHS cell lines, the acidic organelles were markedly clustered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
87
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 43 publications
13
87
0
Order By: Relevance
“…Lyst is a large cytosolic protein containing WD domains at its C terminus (Barbosa et al, 1996). A genetic defect in both lyst and beige, a mouse homologue of lyst, leads to either enlargement and/or dysfunction of lysosome-related organelles, such as melanosomes, dense granules and cytolytic granules (Burkhardt et al, 1993;Shiflett et al, 2002;Ward et al, 2000). Several lines of evidence suggest that the lyst/beige protein is responsible for fission, rather than fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Lyst is a large cytosolic protein containing WD domains at its C terminus (Barbosa et al, 1996). A genetic defect in both lyst and beige, a mouse homologue of lyst, leads to either enlargement and/or dysfunction of lysosome-related organelles, such as melanosomes, dense granules and cytolytic granules (Burkhardt et al, 1993;Shiflett et al, 2002;Ward et al, 2000). Several lines of evidence suggest that the lyst/beige protein is responsible for fission, rather than fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Vesicular transport to and from the lysosome and late endosome is defective in patients with Chediak-Higashi syndrome, and in mutant beige mice (Barbosa et al 1996(Barbosa et al , 1997. In Chediak-Higashi syndrome, and in mutant beige mice, cells have giant, perinuclear vesicles with characteristics of late endosomes and lysosomes that arise from dysregulated homotypic fusion (Brandt et al 1975;Willingham et al 1981;Burkhardt et al 1993). Antisense expression of Rab9 produced cells that contained numerous large vacuoles, a phenotype resembling that of fibroblasts from patients with Chediak-Higashi syndrome (Davies et al 1997).…”
Section: Genomic Structure and Chromosome Mapping Of The Rab9-like Genementioning
confidence: 99%
“…In general, CHS is believed to be a lysosomal disease. It was concluded that giant granules in fibroblasts of beige mice are derived from mature lysosomes and from the late endocytic compartment [15]. Human neutrophils contain several granule subtypes (azurophil, specific, and gelatinase granules), in addition to the highly mobilizable secretory vesicles [for review see ref .…”
Section: Introductionmentioning
confidence: 99%
“…The origin of giant granules has been the subject of intense scrutiny in a variety of cells [1,4,[12][13][14][15]. In general, CHS is believed to be a lysosomal disease.…”
Section: Introductionmentioning
confidence: 99%